SUPERVISORY PRACTICES AMONG MIDDLE LEADERS: A CHRONOLOGICAL REVIEW (2000–2026) - Abdul Patah , Norizan; Mydin, Al-Amin (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
There has been considerable growth in studies of supervisory practices of middle leaders in the last two decades, but little research has examined the chronology of fields of study. This research bridges this gap by examining the chronological development of the field between 2000 and 2026 in terms of the emphasis of the literature, the research methods used, and ideas of the nature of supervision. Using a chronological review, we analysed 101 peer-reviewed journal articles obtained from the Scopus database using a search strategy. The results show a distinct evolution in three phases. Phase 1 (2000-2013) reflected dispersed research, insert into the management narrative. Phase 2 (2014-2019) was a period of consolidation, in which there was increased attention given to instructional leadership, distributed leadership and professional learning. Phase 3 (2020-2026) established exponential growth, with middle leaders considered as instructors, knowledge: Importantly, research designs have transitioned from being largely descriptive to robust and varied designs, such as mixed methods, structural modelling, qualitative, action research, and others. The review shows that supervisory effectiveness is related to personal and organisational factors such as relational skills, trust and organisational support. This confirms the need to enhance preparation and professional development for leaders, and to take more context-sensitive approaches to research, especially in non-Western and longitudinal contexts.